How economic policy uncertainty and financial development contribute to renewable energy consumption? The importance of economic globalization. (January 2023) - Yi, Sun; Raghutla, Chandrashekar; Chittedi, Krishna Reddy; Fareed, Zeeshan
Abstract: Across the globe, many countries have planned to increase renewable energy production capacity by support of financial development, technological innovations and economic policies. Since, using more traditional energy resources produces a large quantity of carbon emissions leading to global warming and climate change. To maintain normal climate and reduce global warming is only possible by shifting the use of traditional energy resources to renewable energy resources. All countries have to give more priority for development of renewable energy which will ensure sustainability and environmental quality. Therefore, this study examines the impact of economic policy uncertainty and financial development on renewable energy consumption by considering role of economic globalization in renewable energy demand function in top renewable energy consuming countries, spanning the period of 2003M01 -2020M12 . We applied panel econometric approaches which handle cross-section dependency, endogeneity and heterogeneity for empirical analysis. The results for long-run and short-run elasticities show that economic growth, financial development and economic globalization have a significant and positive impact on renewable energy consumption. Economic policy uncertainty impedes renewable energy production capacity. Overall, the results suggest that economic globalization, financial development and economic growth significantly increase renewable energy consumption. These results offer new insights for policy-makers to advancement of renewable energy sources by allocation of more capital and transfer of technology for the improvement of environmental quality in top renewable energy consumers. Highlights: We examine the impact of economic globalization on renewable energy consumption. We employ CS-ARDL on panel data from 2003M01 –2020M12 . EG, FD and EG have significant and positive impact on renewable energy consumption. EPU significantly reduces renewable energy consumption.